Effort rights-based management - Squires, Dale; Maunder, Mark; Allen, Robin; Andersen, Peder; Astorkiza, Kepa; Butterworth, Douglas; Caballero, Gonzalo; Clarke, Raymond; Ellefsen, Hans; Guillotreau, Patrice; Hampton, John; Hannesson, Rögnvaldur; et al. (Wiley-Blackwell Publishing, 2017)
Effort rights-based fisheries management (RBM) is less widely used than catchrights, whether for groups or individuals. Because RBM on catch or effort necessar-ily requires a total allowable catch (TAC) or total allowable effort (TAE), RBM isdiscussed in conjunction with issues in assessing fish populations and providingTACs or TAEs. Both approaches have advantages and disadvantages, and there aretrade-offs between the two approaches. In a narrow economic sense, catch rightsare superior because of the type of incentives created, but once the costs ofresearch to improve stock assessments and the associated risks of determining theTAC and costs of monitoring, control, surveillance and enforcement are taken intoconsideration, the choice between catch or effort RBM becomes more complex andless clear. The results will be case specific. Hybrid systems based on both catch andeffort are increasingly employed to manage marine fisheries to capture the advan-tages of both approaches. In hybrid systems, catch or effort RBM dominates and controls on the other supplements. RBM using either catch or effort by itselfaddresses only the target species stock externality and not the remaining externali-ties associated with by-catch and the ecosystem.